The Impact of the "Marriage is Scary" TikTok Trend on Gen Z’s Anxiety Toward Marriage - Hidayah, Nur Aini; Sessiani, Lucky Ade; -, Ikhrom (Psikologi Prima, 2025)
The TikTok Marriage is Scary trend can have a negative impact on Gen Z. The existence of content containing negative narratives causes problems for Gen Z in the form of anxiety. This study aims to determine the impact of the TikTok Marriage is Scary trend on Gen Z in viewing marriage. This research uses a qualitative method with a descriptive approach, data collected through interviews and analysis of videos and comments. Informants in this study were selected by purposive sampling with the following criteria: 13-28 years old (Gen Z), actively using the TikTok application and have seen or been exposed to Marriage is Scary content. The results showed that the TikTok Marriage is Scary trend had an impact on Gen Z's anxiety, stress levels and confidence in marriage. This is further exacerbated by Gen Z's lack of literacy, as well as policy provisions from the TikTok platform that have not been able to select content uploaded on social media. This finding shows the importance of digital literacy so that Gen Z is able to respond to negative content more wisely.